Current update on nanoplatforms as therapeutic and diagnostic tools: A review for the materials used as nanotheranostics and imaging modalities - Panoraia I. Siafaka; Neslihan Üstündağ Okur; Ioannis D. Karantas; Mehmet Evren Okur; Evren Atlıhan Gündoğdu (Elsevier, 2021)
In the last decade, the use of nanotheranostics as emerging diagnostic and therapeutic tools for various diseases, especially cancer, is held great attention. Up to date, several approaches have been employed in order to develop smart nanotheranostics, which combine bioactive targeting on specific tissues as well as diagnostic properties. The nanotheranostics can deliver therapeutic agents by concomitantly monitor the therapy response in real-time. Consequently, the possibility of over- or under-dosing is decreased. Various non-invasive imaging techniques have been used to quantitatively monitor the drug delivery processes. Radiolabeling of nanomaterials is widely used as powerful diagnostic approach on nuclear medicine imaging. In fact, various radiolabeled nanomaterials have been designed and developed for imaging tumors and other lesions due to their efficient characteristics. Inorganic nanoparticles as gold, silver, silica based nanomaterials or organic nanoparticles as polymers, carbon based nanomaterials, liposomes have been reported as multifunctional nanotheranostics. In this review, the imaging modalities according to their use in various diseases are summarized, providing special details for radiolabeling. In further, the most current nanotheranostics categorized via the used nanomaterials are also summed up. To conclude, this review can be beneficial for medical and pharmaceutical society as well as material scientists who work in the field of nanotheranostics since they can use this research as guide for producing newer and more efficient nanotheranostics.